Direct Torque Control of IPMSMs for Fast Dynamic Response with Constant Switching Frequency - Shin, Eun Kyeol; Lee, Kyo Beum (Transactions of the Korean Institute of Electrical Engineers, 2023)
This paper proposes the direct torque control (DTC) of interior permanent magnet synchronous motors (IPMSMs) for fast dynamic response with constant switching frequency. The conventional DTC is constructed based on the hysteresis flux and torque controllers with the flux and torque errors as input. The switching frequency of DTC is not constant. In the DTC with constant switching frequency, a torque regulator with a constant switching frequency is applied to overcome this problem, instead of the hysteresis torque controller for the conventional DTC. The DTC with constant switching frequency uses a torque regulator with a proportional-integral (PI) torque controller and a triangular carrier to realize a constant switching frequency. Compared to the conventional DTC, the DTC with constant switching frequency has the poor dynamic response because both voltage vectors increasing and decreasing torque are selected in the transient state. In this paper, the bandwidth of PI torque controller is varied to improve the dynamic response of the DTC with constant switching frequency. The effectiveness of the proposed method is verified through simulation results.
Keywords: Constant switching frequency; Direct torque control; Fast dynamic response; Flux controllers; Interior permanent magnet synchronoi motor; Interior permanent magnet synchronous motor; Proportional integral; Torque controllers; Voltage vectors; Constant switching frequency; Direct torque control (DTC); Dynamic response; Interior permanent magnet synchronous motor (IPMSM)